Ethnic Cleansing and Post-Traumatic Coping - War Violence, PTSD, Depression, Anxiety and Coping in Bosnian and Croatian Refugees. A transactional Approach - Arcel, Libby Tata; Folnegović-Šmalc, Vera; Tocilj-Šimunković, Gorana Kozarić-Kovačić, Dragica; Ljubotina, Damir (1998)
The article provide an overall picture of the refugee population treated in Boswofam from 1993 to 1995. Socio-demographic characteristics of 2023 persons are presented. For a sample of 402 persons research data regarding PTSD, anxiety and depression are shown. The results showed that nearly 40% of the population had no symptoms or only mild symptoms, while approximately 60% had in varying degrees of mental health symptoms. Coping strategies correlated with absence or presence of well-being were identified.
Projekt MZOS
ENG